Egon Vielrose (1907–1984) – Demographer, Statistician, Econometrician - Domański, Czesław (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Egon Vielrose was an outstanding Polish demographer, statistician and econometrician. He studied mathematics at Warsaw University and economics at the Higher School of Trade and then he qualified as an assistant professor at Warsaw University. His research interests focused on problems of demography, mathematical statistics, econometrics and socio‑economic statistics. An important place in the work of Egon Vielrose is occupied by studies in historic demography, concerning mostly the natural movement which is a decisive factor in population development. The scientific output of Egon Vielrose encompasses over 200 works including 6 books and over 130 papers.